Optimization of structural design for sustainable construction of transmission tower based on topographical algorithm - Muda Z.C.; Mustapha K.N.; Omar R.C.; Usman F.; Alam M.A.; Thiruchelvam S. (Institute of Physics Publishing, 2023)
Optimization of transmission tower structures is traditionally based on either optimization of members sizes with fixed topographical shape or based on structural analysis modelling strategies without taking cognizance of fabrication and constructability issue facing the contractors . This paper look into an integrated optimum design approach strategies whereby size, shape and topology are combined together with the fabrication issues in the construction of the transmission tower. The topographical algorithm is based on changing the inclination degree of the legs of the tower at first with optimum individual members sizing and later rationalized member sizes are performed through member groupings for the ease fabrication and construction of the transmission tower. The optimum weight using topographical algorithm obtained for the transmission tower is 10,924 kg for singular members and 18,430 kg for element grouping at 10 inclination angle. Published under licence by IOP Publishing Ltd.